COLLECTIVE TRAUMA IN REFUGEE LITERATURE (BASED ON ALMANACS – 14 GIGABYTES AND HALLELUIAH) - Nino Mindiashvili,; Nana Kutsia, (International Journal of Innovative Technologies in Social Science, 2021)
Theories of traumatic memory are uniquely topical in modern theoretical discourse, Collective trauma is a complex of psychological sensations, which is formed in witnesses or participants of tragic events, who have to deal with psychological stigma. Theoretical framework about the collective trauma is relevant to events that have taken place in Georgia, as the epochal tragedy has changed ethnic and cultural environment in Abkhazia and Tskhinvali Region. As the subject of research, we have defined the almanacs reflecting Georgian-Abkhazian and Georgian-Ossetian (provoked by the third force) conflicts: 14 Gigabytes and Halleluiah. Uniqueness of 14 Gigabytes is reasoned by the concept set by the editor (Nana Gaprindashvili) and the complier of the almanac (Tea Kalandia) – 14 narrators tell about the Abkhazian episode of Russian-Georgian war. Personal stories create the monumental canvas-reflection of the feelings of youth who have been deprived of childhood. Authors of the poetic almanac Halleluiah published in 2018, under the editorship of Mzia Khetaguri, are united under refugee stigma, pain caused by losing homes, trauma, which marks each of the texts like an unhealed wound. It must be emphasized that in none of the researched authors’ texts reflects hostility or aggression towards “conflicting sides” or even the main provoking power – Russia. The presented discourse allows us to confirm the research hypothesis: conflicts provoked by Russia have forced Georgian population of Abkhazia and Tskhinvali Region to leave their homes, to go through the horrors of war. Refugees have to deal with the stigma of being refugees and grave experience of collective trauma, which is creatively transformed, reflexed in the almanacs 14 Gigabytes and Halleluiah.